Bio-inspired networking - Câmara, Daniel (ISTE Press, Ltd. Elsevier Ltd, 2015)
Bio-inspired techniques are based on principles, or models, of biological systems. In general, natural systems present remarkable capabilities of resilience and adaptability. In this book, we explore how bio-inspired methods can solve different problems linked to computer networks